Framed by gender how gender inequality persists in the modern world - Ridgeway, Cecilia L. (New York ; Oxford : Oxford University Press, 2011)
Ridgeway asserts that widely shared cultural beliefs about gender act as a 'common knowledge' frame that people use to make sense of one another in order to coordinate their interaction.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sex role -- United States; Social interaction -- United States; Women -- Social conditions; Women -- Economic conditions; Equality -- United States